A case study on the effect of an energy recovering rudder bulb-turbine device on ship powering characteristics. (13th September 2020) - Wang, Chunhui; Guo, Chunyu; Wang, Chao; Han, Fenglei
ABSTRACT: A novel energy saving device, namely a rudder bulb-turbine device (RBTD), is proposed, which consists of turbine blades, a rudder bulb, a transmission shaft, a generator, and a variable-frequency drive. The propeller wake affects the turbine blade and causes it to rotate together with the head of the rudder bulb and to drive the generator inside the rudder to produce electricity, thereby recovering the rotational energy of the propeller wake. Computations are conducted in towing, propeller open-water, and self-propulsion conditions for a 9200TEU containership to explore the effect of the RBTD. The results show that the RBTD has a positive effect on the powering characteristics and the extractable power of the RBTD generator is approximately equal to that of a small generator installed in a large containership. It can also significantly suppress the tangential motion in the wake of the propeller and has favorable interference to the hull.